2019
DOI: 10.3389/fcell.2019.00254
|View full text |Cite
|
Sign up to set email alerts
|

The Microenvironment Is a Critical Regulator of Muscle Stem Cell Activation and Proliferation

Abstract: Skeletal muscle has a remarkable capacity to regenerate following injury, a property conferred by a resident population of muscle stem cells (MuSCs). In response to injury, MuSCs must double their cellular content to divide, a process requiring significant new biomass in the form of nucleotides, phospholipids, and amino acids. This new biomass is derived from a series of intracellular metabolic cycles and alternative routing of carbon. In this review, we examine the link between metabolism and skeletal muscle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 124 publications
(144 reference statements)
0
29
0
Order By: Relevance
“…Skeletal muscle constitutes a significant percentage of total body mass and is indispensable to physical movements, maintaining postures and in vital actions (Diaz-Vegas et al, 2019;Hood et al, 2019). It is also a primary peripheral tissue important for utilizing glucose and fatty acid for energy generation essential for the prevention of obesity and type 2 diabetes (Dumont et al, 2015a;Nguyen et al, 2019). It is made up of thousands of long and cylindrical multinucleated muscle fibers surrounded by the sarcolemma, a lipid bi-layer membrane that attaches a complex extracellular matrix, which is in contact with the basement membrane (Dumont et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…Skeletal muscle constitutes a significant percentage of total body mass and is indispensable to physical movements, maintaining postures and in vital actions (Diaz-Vegas et al, 2019;Hood et al, 2019). It is also a primary peripheral tissue important for utilizing glucose and fatty acid for energy generation essential for the prevention of obesity and type 2 diabetes (Dumont et al, 2015a;Nguyen et al, 2019). It is made up of thousands of long and cylindrical multinucleated muscle fibers surrounded by the sarcolemma, a lipid bi-layer membrane that attaches a complex extracellular matrix, which is in contact with the basement membrane (Dumont et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, previous clinical trials with MPCs showed variable cell numbers, different injection modes and the use of different substances, and possibly therefore led to variable outcomes. The next important point is the microenvironment for the non-muscle derived stem cells [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Muscle tissues that require contractile activity for proper functioning, could also be repaired or replaced by the means of TE, such as the various sphincters, bladder, intestine, diaphragm, face, hand, tongue, pharynx, larynx and oesophagus. In general, TE uses progenitor cells in combination with suitable biomaterials that together generate the appropriate microenvironment to functionally repair, replace and regenerate the damaged or lost organ [ 1 , 2 ]. However, production of engineered tissues and organs requires the use of large number of cells.…”
Section: Introductionmentioning
confidence: 99%
“…One larger subpopulation would consist of SCs with a higher myogenic differentiation potential that readily undergo activation and proliferation after injury, while the other one would be mainly responsible for SC pool maintenance to ensure tissue regeneration in case of subsequent injuries. 154,155 In their quiescent state, satellite cells are specifically located between the basal lamina, which protects them from the surrounding milieu, and the sarcolemma of skeletal myofibers. 136 Muscle repair/regeneration upon damage is a tightly orchestrated process that begins with an inflammatory response followed by tissue necrosis, and then satellite cell activation, expansion, migration, differentiation, and fusion to restore injured myofibers or generate new myofibers.…”
Section: The Skeletal Muscle Sc Niche Microenvironment Before the Identification Of Tcsmentioning
confidence: 99%